Motivating change-oriented behavior through coaching leadership: the role of psychological entitlement and knowledge management - Hu, Jiaming; Choi, MyeongCheol; Kim, Hann Earl (Frontiers in Psychology, 2025)
IntroductionIn today’s fast-changing organizational environment, leadership styles such as coaching leadership are attracting attention for their potential to inspire innovative and proactive behaviors among employees. Coaching leadership focuses on employee development, motivation, and support, which makes it an ideal leadership style to address organizational challenges and drive change. This study examines the mediating roles of knowledge management and psychological entitlement in the relationship between coaching leadership and employee change-oriented behavior.MethodsBased on the data analysis of 492 respondents from the hospitality industry in China, this study used structural equation modeling to test the hypotheses.ResultsThe findings suggest that coaching leadership significantly influences knowledge management and psychological entitlement, which further mediate the role of coaching leadership on change-oriented behavior. Specifically, knowledge management provided employees with important tools and resources needed to drive change, while psychological entitlement facilitated change behavior by enhancing employees’ intrinsic motivation and responsibility.DiscussionThis study deepens the understanding of the mechanisms between leadership style and change-oriented behavior, emphasizing the key roles of knowledge management and psychological entitlement. Practical implications include enhancing organizational adaptability and innovation by creating an empowering culture and optimizing systems. Future studies should expand the diversity of the sample and adopt a longitudinal research approach to capture dynamic causal relationships.